Lipoid proteinosis: identification of a novel nonsense mutation c.1246C>T:p.R416X in ECM1 gene from Bangladesh - Khan, Md. Azraf Hossain; Reza, Md. Abu; Md. Sharaf, Ibrahim; Alam, Md. Jahangir; Rahman, Md. Mostafizur; Chandra, Pampa; Anwar, Kazi Selim; Salam, Md. Abdus (Professional Medical Publications, 2023)
Lipoid proteinosis is a rare multisystem genodermatosis inherited as autosomal recessive trait. We report a case of lipoid proteinosis in a 10-year-old boy born to first-degree consanguineous parents presented with marked hoarseness of voice, accelerated photoaging appearance, enlarged and erythematous tongue with restricted movement and widespread dermatoses. Biopsy of oral mucosa revealed Periodic acid-Schiff (PAS)-positive amorphous eosinophilic hyaline deposits. Mutational analysis revealed a homozygous nonsense mutation with C to T substitution at nucleotide position 1246(c.1246C>T) in exon-8 of the extracellular matrix protein 1 gene leading to a stop codon. Both the parents were unaffected heterozygous carriers. To our knowledge, this is the first case report of lipoid proteinosis with evidence of a novel nonsense genetic mutation from Bangladesh.